Exposure level of human receptors to respirable particulate in Universiti Sains Malaysia, Tronoh [Malaysia] - Nor Azam Ramli (Penerbit Universiti Sains Malaysia, 2015)
Measurement of respirable particulate fractions concentrations were made in Universiti Sains Malaysia, Tronoh in July 2000. In environmental set-up like Tronoh, particulate matter is the most likely dominant contributor to airbone pollutants. Time series patterns of the respirable particulate fractions indicate relationships with human-related activities. Traffic volume relationships with temporary elevated levels of respirable particulate fractions were not causal. Exposure levels of human receptor to respirable particulate fractions were observed to reach the highest not necessarily during peak traffic hours. Windspeed and wind directions were important particulate matter (PM) dispersion factors.